Relationship between the entrance score and the academic performance of the students of the Faculty of Mathematical Sciences of the UNMSM who entered through the admission exams 2010-2013 - Gonzales Bohorquez, Martha Olinda (2018)
The present study examines the relationship between the entrance examination score and the academic performance coefficient (CRA) of a population made up of the students of the Faculty of Mathematical Sciences who through the admission exams 2010 - 2013 of the UNMSM were admitted in the FCM. Through the CRA, the study population was classified according to academic performance, showing that more than 80% of the population classifies as a student at academic risk. For each stratum of the population, contingency tables were prepared and the Pearson correlation coecient was used to study the relationship between the income score and the ARC. The results obtained showed that those who entered with the highest scores to the FCM are not necessarily those who have better academic performance in the first two years of study, but those who are more likely to classify as a student with average or higher performance. smallskip.